Percabangan retak sebagai bentuk penahanan perambatan retak fatik pada bahan perunggu keras - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Hard bronze is a metal alloy consisting of 15%-20% tin (Sn) and 80 %-85% copper (Cu).This alloy is well known because its hardness and its high corrosion resostent.Unfortunately this material is brittle and is easily broken or cracked in its application.The Perpose of this research is to improve the ability of this material to reduce the fatigue crack growth rate or even to materialo was prepared with casting process and continued with press forging in temperature 700C, with three variation of forging reduction those were 10%, 20%, and 30% of each.The fatigue crack growth rate test was conducted under shimadzu universal testing Machine with stress ratio (R) of 0.3 and frequensy 5-11 Hz. The Experimental result shows that the forging product with the low forging reduction (!0%) have the best ability to retard the crack growth rate.This retardation is caused by the existence of crack bifurcation or crack branching. Key Words:Hard bronze, Fiatigue crack growth rate, bifurcation